Ascospore Formation in the Yeast Saccharomyces cerevisiae - Neiman, Aaron M. (American Society for Microbiology, 2005)
Sporulation of the baker's yeast Saccharomyces cerevisiae is a response to nutrient depletion that allows a single diploid cell to give rise to four stress-resistant haploid spores. The formation of these spores requires a coordinated reorganization of cellular architecture. The construction of the spores can be broadly divided into two phases. The first is the generation of new membrane compartments within the cell cytoplasm that ultimately give rise to the spore plasma membranes. Proper assembly and growth of these membranes require modification of aspects of the constitutive secretory pathway and cytoskeleton by sporulation-specific functions. In the second phase, each immature spore becomes surrounded by a multilaminar spore wall that provides resistance to environmental stresses. This review focuses on our current understanding of the cellular rearrangements and the genes required in each of these phases to give rise to a wild-type spore.